Impact of size and thermal gradient on supercooling of phase change materials for thermal energy storage. (15th May 2021) - Lilley, Drew; Lau, Jonathan; Dames, Chris; Kaur, Sumanjeet; Prasher, Ravi
Highlights: System size and heat transfer impact supercooling behavior in phase change materials. Supercooling can be experimentally characterized in differential scanning calorimetry and predicted in larger systems. A new supercooling model can be incorporated into existing phase change material computational models. A new standardized definition of supercooling for thermal energy storage is suggested. Supercooling predictive model is validated experimentally using Neopentyl Glycol. Abstract: Phase change material based thermal energy storage has many current and potential applications in the heating and cooling of buildings, battery and electronics thermal management, thermal textiles, and dry cooling of power plants. However, connecting lab scale thermal data obtained with differential scanning calorimetry (DSC) to the performance of large-scale practical systems has been a major challenge primarily due to the dependence of supercooling on the size and temperature gradient of the system. In this work we show how a phase change material's supercooling behavior can be characterized experimentally using common lab scale thermal analysis techniques. We then develop a statistics based theoretical model that uses the lab-scale data on small samples to quantitatively predict the supercooling performance for a general thermal energy storage application of any size, including also allowing for the possibility of temperature gradients. Finally, we validate the modeling methodology by comparing to experimental results for solid-solid phase change in neopentyl glycol, which shows how the model successfully predicts the changes in supercooling temperature across a large range of cooling rates (2 orders of magnitude) and volumes (3 orders of magnitude). By accounting for thermal gradients, the model avoids 2x error incurred by lumped approximations.